Unveiling Producers' Experiences in Adopting Cloud and the Revolution of Broadcasting Content Production - Farid, Ahmad Salman (Proceedings of International Conference on Da'wa and Communication, 2024)
This study examines the adoption of cloud technologies by producers in the broadcasting industry, with a focus on how these innovations are transforming content production. As the industry increasingly shifts towards cloud-based solutions, understanding the experiences of industry professionals becomes crucial, especially regarding the benefits and challenges they face. A qualitative research approach was employed, utilizing in-depth interviews with broadcasting producers who have substantial experience with cloud technologies in content production. The analysis revealed that cloud technologies significantly enhance the flexibility and scalability of production processes, enabling dynamic resource management. Producers reported notable cost savings due to optimized resource allocation and reduced infrastructure expenses. The study also highlighted enhanced collaboration, with cloud platforms facilitating real-time remote production and fostering creative synergy among dispersed teams. However, concerns over security, intellectual property protection, and regulatory compliance were pervasive, underscoring the need for robust security measures. Additionally, the transition to cloud-based workflows requires a shift in skillsets and operational strategies among producers. While cloud adoption is driving significant transformation in the broadcasting industry, the management of associated risks is critical for sustaining these advancements. The ongoing evolution of cloud technologies promises continued innovation in content production, with far-reaching implications for the future of broadcasting.